Assessment of Exercise Capacity and Oxygen Consumption Using a 6 min Stepper Test in Older Adults - Jones, Siana; Tillin, Therese; Williams, Suzanne; Coady, Emma; Chaturvedi, Nishi; Hughes, Alun D. (Frontiers in Physiology, 2017)
It is often necessary to assess physical function in older adults to monitor disease progression, rehabilitation or decline in function with age. However, increasing frailty and poor balance that accompany aging are common barriers to exercise testing protocols. We investigated whether a 6-minute stepper test (6MST) was acceptable to older adults and provided a measure of exercise capacity and a predicted value for peak aerobic capacity (VO2max). 635 older adults from a tri-ethnic UK population-based cohort were screened to undertake a self-paced 6MST. Expired gas analysis, heart rate and blood pressure monitoring were carried out. A sub-set of 20 participants performed a second 6MST for assessment of reproducibility and a further sub-set of 10 performed the 6-minute walk test as verification against a well-recognized and accepted self-paced exercise test. 518 (82%) participants met inclusion criteria and undertook the 6MST (299 men, mean age 71.2±6.4). Step rate showed a strong positive correlation with measured VO2 (r=0.75, p < 0.001) and VO2 was lower in women (male-female difference in VO2= 2.61 (95% confidence interval 3.6, -1.7) ml/min/kg; p<0.001). 20 participants repeated a 6MST, step rate was higher in the second test but the predicted VO2max showed good agreement (mean difference=0.1 [3.72, 3.95] ml/min/kg). In 10 participants who completed a 6MST and a 6-minute walk test there was a strong positive correlation between walking rate and step rate (r=0.77; p<0.009) and weaker positive correlations between the tests for measured VO2 and peak heart rate. In conclusion, the 6MST is a convenient, acceptable method of assessing exercise capacity in older adults that allows VO2max to be predicted reproducibly. The test shows good correlation between performance and measured physiological markers of performance and can detect the expected gender differences in measured VO2. Furthermore, the 6MST results correlate with a previously verified and established self-paced exercise test.